Context and Implications Document for: The research on educational leadership and management in the Arab world since the 1990s: A systematic review. Issue 3 (5th May 2017) - Oplatka, Izhar; Arar, Khalid
Abstract : This guide accompanies the following article: Oplatka, I. & Arar, K., The research on educational leadership and management in the Arab world since the 1990s: A systematic review. Review of Education, https://doi.org/10.1002/rev3.3095